#### Answer

-4

#### Work Step by Step

"Double the sum of a number and 6" translates to 2(x + 6).
"the opposite of the number" translates to -x.
Therefore, the equation is 2(x + 6) = -x
Solve for x:
2x + 12 = -x
3x + 12 = 0
3x = -12
x = -4

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

-4

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.